(untitled) (Nonconventional Technologies Review, 2019)
Cosmetic textiles are a new generation of textiles describing high-tech fabrics that incorporate personal care ingredients, which can impart skincare benefits, combating ageing, feeling of wellness or well-being, such as slimming, perfume, or moisturizing. Researches in this domain found that essentials oils had more than a therapeutic effect and could involve sales and marketing. Essential oils are natural bio-based multicomponent products containing active agents responsible for antibacterial activity, refreshing, relaxing, calming, balancing, causing euphoria and providing astringent, antiseptic, decongestant, therapeutic, toning, fortifying, cooling properties and so on. As people are used to wear textile materials in their daily life thus it is also logical to use textile as the possible basis for the delivery system of cosmetic or pharmaceutical ingredients leading to a controlled release for skincare benefits. In this respect, this study approached the experimentation of deposition by electro-spraying method of commercial rosemary microcapsules on woven cotton fabrics. An acrylate-based binder was used to improve the durability to external factors. The finished textile materials were characterized in terms of physical-mechanical and comfort characteristics. The distribution of microcapsules on the fabric surface was investigated by SEM analysis.